Exploring the chemical and pharmacological variability of Lepidium meyenii: a comprehensive review of the effects of maca - Ulloa del Carpio, Norka; Alvarado-Corella, Diego; Quiñones-Laveriano, Dante M.; Araya-Sibaja, Andrea; Vega-Baudrit, José; Monagas-Juan, Maria; Navarro-Hoyos, Mirtha; Villar-López, Martha (Frontiers in Pharmacology, 2024)
Maca (Lepidium meyenii), a biennial herbaceous plant indigenous to the Andes Mountains, has a rich history of traditional use for its purported health benefits. Maca's chemical composition varies due to ecotypes, growth conditions, and post-harvest processing, contributing to its intricate phytochemical profile, including, macamides, macaenes, and glucosinolates, among other components. This review provides an in-depth revision and analysis of Maca's diverse bioactive metabolites, focusing on the pharmacological properties registered in pre-clinical and clinical studies. Maca is generally safe, with rare adverse effects, supported by preclinical studies revealing low toxicity and good human tolerance. Preclinical investigations highlight the benefits attributed to Maca compounds, including neuroprotection, anti-inflammatory properties, immunoregulation, and antioxidant effects. Maca has also shown potential for enhancing fertility, combating fatigue, and exhibiting potential antitumor properties. Maca's versatility extends to metabolic regulation, gastrointestinal health, cardio protection, antihypertensive activity, photoprotection, muscle growth, hepatoprotection, proangiogenic effects, Frontiers in Pharmacology www.frontiersin.com antithrombotic properties, and antiallergic activity. Clinical studies, primarily focused on sexual health, indicate improved sexual desire, erectile function, and subjective well-being in men. Maca also shows promise in alleviating menopausal symptoms in women and enhancing physical performance. Further research is essential to uncover the mechanisms and clinical applications of Maca's unique bioactive metabolites, solidifying its place as a subject of growing scientific interest.